The Moderating Effect of Job Satisfaction to Work Motivation and Employees’ Performance - Majid, Abdul; Fajri, Mega Barokatul; Assadam, Elvina; Febrianti, Devi (Publisher Cv. Inara, 2021)
Work satisfaction and motivation have been believed to directly connect to employee performance. These two indicators are potential to either decrease or increase the level of performance, how many items an employee can meet in an accordance with company terms. Employee with well-satisfaction may be motivated to show up their maximum performance while working, which consequently increase company performance or organization after all. This study aims to analyze job satisfaction in moderating the effect of work motivation on employee performance. This research uses a quantitative research approach by means of a survey research. The population of this study were all employees of Hotel Paradise Batu, so that the sampling used total sampling technique. Descriptive data and moderated regression were used as data analysis. The results show that work motivation has an effect on employee performance, work motivation and satisfaction have a positive and significant effect on employee performance, and job satisfaction moderates the interaction of work motivation and employee performance